Predicting Baker's Yeast Dosage and Fermentation Time on Bioethanol Production Made from Papaya Skin Waste - I Nengah Muliarta; Ni Luh Putu Putri Setianingsih Ni Luh Putu Putri Setianingsih, S.Si., M.Si.; Wayan Sudiarta Ir. Wayan Sudiarta, MP; Desak Ayu Diah Prawerti Desak Ayu Diah Prawerti; I Kadek Somariana I Kadek Somariana; I Ketut Suwarmadi Putra I Ketut Suwarmadi Putra (Formosa Journal of Sustainable Research, 2023)
This literature study research aims to find the appropriate yeast dose and fermentation time to process papaya skin waste into bioethanol by utilizing Saccharomyces cerevisiae yeast. Papaya skin waste is one of the biomass that is quite abundant and contains high sugar content so it can be used as raw material for making bioethanol. The data collection method was carried out through online searches of scientific journals related to the potential of papaya waste, fermentation, bioethanol production, bioethanol manufacturing techniques, yeast types and yeast doses, and bioethanol content. As a result, get fermentation for making bioethanol efficiently using a yeast dose of 0.3% and the fastest fermentation time of 3 days